Projeto e fabricação de kit didático voltado a robótica educacional - Raposo, Luciana Queiroz (2021)
In view of the contemporary growing demand for intellectual capital, which is built from the skills of the 21st century, educational robotics presents itself in the current scenario as a cognitive tool capable of developing necessary to satisfy the new demands of the technological and digital world. However, the major obstacle for the propagation of this educational tool in many countries is the cost of technological solutions employed by educational robotics, and also its simplicity. Thus, this work’s objective was to offer an alternative, low-cost and simple-to-use technological solution. The product developed was an educational robotics kit, produced with the aid of additive manufacturing (3D printing) and the use of electronic components (actuators, microcontroller and sensor). The robotics kit was divided into two modules, of which: module I, based on analog electronics, is intended for (3 to 5 years old) while module II, based on analog and digital electronics, is intended for elementary school students. Each module included the production of a lesson plan that included a pedagogical practice for application with students. The kit was applied with preschool children and 1st and 2nd elementary school students (aged 3 to 7 years), with students from two private schools in the city of Natal/RN. The application designed for module I, called FoxCar, demonstrated the module's ability to act as a four-wheeled car controlled by a four-button remote control, and perform movements in all directions. For module II, the proposed activity (called "Conscious Traffic Light") performed, through the BBC Micro:bit microcontroller, a simulation of a traffic light. The students worked with plugged programming in blocks in order to program the traffic lights colors (green, yellow and red) with a timer and in the correct sequence. In general, both modules worked as expected, and their application in the classroom contributed to the teaching of robotics, electronics and programming concepts in an interdisciplinary way with other areas of knowledge. Future improvements should be made to both modules in order to make it more attractive and functional.